The Home as a Place of Work - Who Cares and Why? - Friederike Molitor (Social Sciences, 2024)
As demand for privately organized care and domestic work has grown, digital platforms have emerged as key intermediaries connecting prospective workers with clients. Drawing on unique survey data collected in Germany in 2019, this study offers a systematic analysis of the sociodemographic characteristics of platform-mediated care and domestic workers, with particular focus on their family and household compositions and their motivations for using a digital care-work platform. The study's findings reveal similarities between these workers, traditional care and domestic workers, and other platform workers in the gig economy. This study also focuses on how this work serves as a strategy for reconciling paid work with unpaid family responsibilities. Importantly, a noticeable proportion of the workers have unpaid care responsibilities for children or other family members and friends while pursuing platform work. When asked about their reasons for using a digital platform, the workers mostly name the income potential, job flexibility, and independence that this platform-mediated work provides. However, the motivations of different groups of workers vary: those with children more often value the balance of paid work and family life that this work offers, while financial incentives and professional development are less of a priority.
Keywords: 320; care and domestic work; gender; informality; gig economy